GENDER IN ISLAMIC PERSPECTIVE: RESEARCH ON THE INTERPRETATION OF VERSES AND HADITH FROM A GENDER PERSPECTIVE - Ridwan; Sofia Hardani (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study examines gender in the perspective of Islam through a review of Qur’anic verses and Hadiths with a gender-sensitive approach. The purpose of this research is to analyze how Islamic texts address gender equality, women’s rights, and the social roles of men and women. A qualitative literature review method was employed, focusing on Tafsir (Qur’anic exegesis) and Hadith analysis. The findings show that while traditional interpretations often emphasize gender differences, many verses and Hadiths affirm equal rights and responsibilities for men and women when interpreted through a gender perspective. The study highlights that gender-sensitive interpretation of Islamic texts can promote social justice, women’s empowerment, and inclusive religious understanding. This research contributes to a broader discourse on contextualizing Islamic teachings in modern gender studies.